Tabu search for the RNA partial degradation problem - Rybarczyk, Agnieszka; Hertz, Alain; Kasprzak, Marta; Blazewicz, Jacek (Zielona Góra: Uniwersytet Zielonogórski)
In recent years, a growing interest has been observed in research on RNA (ribonucleic acid), primarily due to the discovery of the role of RNA molecules in biological systems. They not only serve as templates in protein synthesis or as adapters in the translation process, but also influence and are involved in the regulation of gene expression. The RNA degradation process is now heavily studied as a potential source of such riboregulators.
Keywords: RNA degradation; tabu search; bioinformatics